Dacomitinib‐induced diarrhea: Targeting chloride secretion with crofelemer. Issue 2 (28th September 2017) - Van Sebille, Ysabella Z.A.; Gibson, Rachel J.; Wardill, Hannah R.; Ball, Imogen A.; Keefe, Dorothy M.K.; Bowen, Joanne M.
Abstract : Dacomitinib, an irreversible small‐molecule pan‐ErbB TKI, has a high incidence of diarrhea, which has been suggested to be due to chloride secretory mechanisms. Based on this hypothesis, crofelemer, an antisecretory agent may be an effective intervention. T84 monolayers were treated with 1 µM dacomitinib and 10 µM crofelemer, and mounted into Ussing chambers for electrogenic ion analysis. Crofelemer attenuated increases in chloride secretion in cells treated with dacomitinib. Albino Wistar rats ( n  = 48) were treated with 7.5 mg/kg dacomitinib and/or 25 mg/kg crofelemer via oral gavage for 21 days. Crofelemer significantly worsened dacomitinib‐induced diarrhea ( p  = 0.0003), and did not attenuate weight loss ( p  < 0.0001). Sections of the ileum and colon were mounted into Ussing chambers, and secretory processes analyzed. This indicated that crofelemer lost its anti‐secretory action in the presence of dacomitinib in this model. Mass spectrometry revealed that crofelemer did not change serum concentration of dacomitinib. Serum FITC dextran levels indicated that crofelemer was unable to attenuate dacomitinib‐induced barrier dysfunction. Tight junction proteins were visualized with immunofluorescence. Qualitative analysis showed dacomitinib induced proteolysis of ZO‐1 and occludin, and internalization of claudin‐1, which was not attenuated by crofelemer. Detailed histopathological analysis showed that crofelemer was unable to attenuate dacomitinib‐induced ileal damage. Crofelemer worsened dacomitinib‐induced diarrhea, suggesting that antisecretory drug therapy may be ineffective in this setting. Abstract : What's new? Dacomitinib, an irreversible inhibitor of the ErbB receptor tyrosine kinase, induces diarrhea in about three‐quarters of patients, potentially leading to treatment discontinuation. Diarrhea is suspected to result from effects on chloride secretory mechanisms. The present preclinical study investigated the possibility of using crofelemer, an antisecretory antidiarrheal agent with inhibitory effects on chloride channels, as a prophylactic in patients taking dacomitinib. In cells, crofelemer reduced dacomitinib‐induced elevations in chloride secretion. Rats treated with dacomitinib and crofelemer combined, however, experienced severe diarrhea more often than dacomitinib‐only treated animals. The findings suggest that crofelemer may have contraindications in dacomitinib‐treated patients.